Gender and Climate Change in Bangladesh : The Role of Institutions in Reducing Gender Gaps in Adaptation Program - Ahmad, Nilufar (Washington, DC, 2017)
This study on Bangladesh was undertaken to analyze the gender dimensions of climate change and the role of institutions in reducing gender gaps. The study was carried out in 20 sites covering 600 households, from March 2010 to May 2011, using both qualitative and quantitative instruments. This note is organized into five sections. The next section gives an overview of climate change and the gender and institutional context in Bangladesh. The third section presents the key study findings and is divided into three subsections: site- and household-specific vulnerabilities; analysis of gender dimensions of climate change using the household data and four propositions; and description of institutional challenges and gaps in supporting the resilience of women and men. Section four provides examples of adaptation programs in Bangladesh, and section five provides recommendations for enhancing gender-responsive adaptive capacity in Bangladesh.